Energy independence of the Collins asymmetry in p ↑ p collisions - STAR Collaboration (Physical Review Letters, 2025)
The STAR experiment reports new, high-precision measurements of the transverse single-spin asymmetries for π{±} within jets, namely the Collins asymmetries, from transversely polarized p{↑}p collisions at sqrt[s]=510 GeV. The energy-scaled distribution of jet transverse momentum, x_{T}=2p_{T,jet}/sqrt[s], shows a remarkable consistency for Collins asymmetries of π{±} in jets between sqrt[s]=200 GeV and 510 GeV. This indicates that the Collins asymmetries are nearly energy independent, with, at most, a very weak scale dependence in p{↑}p collisions. These results extend to high-momentum scales (Q{2}≤3400 GeV{2}) and enable unique tests of evolution and universality in the transverse-momentum-dependent formalism, thus providing important constraints for the Collins fragmentation functions.
Keywords: Asymmetry; Consistency (knowledge bases); Fragmentation (computing); High energy; Independence (probability theory); Polarization (electrochemistry); Transverse plane; Universality (dynamical systems); dept.phy

Collision-System and Beam-Energy Dependence of Anisotropic Flow Fluctuations - STAR Collaboration (Physical Review Letters, 2022)
Elliptic flow measurements from two-, four-, and six-particle correlations are used to investigate flow fluctuations in collisions of U+U at √sNN=193 GeV, Cu+Au at √sNN=200 GeV and Au+Au spanning the range √sNN=11.5–200 GeV. The measurements show a strong dependence of the flow fluctuations on collision centrality, a modest dependence on system size, and very little if any, dependence on particle species and beam energy. The results, when compared to similar LHC measurements, viscous hydrodynamic calculations, and trento model eccentricities, indicate that initial-state-driven fluctuations predominate the flow fluctuations generated in the collisions studied.
0 citations (Crossref) [2023-10-31] arXiv: http://arxiv.org/pdf/2201.10365
Keywords: dept.phy; peer-reviewed

Jet-hadron correlations with respect to the event plane in sNN =200 GeV Au+Au collisions in STAR - STAR Collaboration (Physical Review C, 2024)
Angular distributions of charged particles relative to jet axes are studied in sNN=200 GeV Au+Au collisions as a function of the jet orientation with respect to the event plane. This differential study tests the expected path-length dependence of energy loss experienced by a hard-scattered parton as it traverses the hot and dense medium formed in heavy-ion collisions. A second-order event plane is used in the analysis as an experimental estimate of the reaction plane formed by the collision impact parameter and the beam direction. Charged-particle jets with 15<pT,jet<20 and 20<pT,jet<40GeV/c were reconstructed with the anti-kT algorithm with radius parameter setting of R=0.4 in the 20-50% centrality bin to maximize the initial-state eccentricity of the interaction region. The reaction plane fit method is implemented to remove the flow-modulated background with better precision than prior methods. Yields and widths of jet-associated charged-hadron distributions are extracted in three angular bins between the jet axis and the event plane. The event-plane (EP) dependence is further quantified by ratios of the associated yields in different EP bins. No dependence on orientation of the jet axis with respect to the event plane is seen within the uncertainties in the kinematic regime studied. This finding is consistent with a similar experimental observation by ALICE in sNN = 2.76 TeV Pb-Pb collision data. © 2024 American Physical Society.
Keywords: dept.phy; peer-reviewed

Results on elastic cross sections in proton–proton collisions at s=510 GeV with the STAR detector at RHIC - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2024)
We report results on an elastic cross section measurement in proton–proton collisions at a center-of-mass energy s=510 GeV, obtained with the Roman Pot setup of the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The elastic differential cross section is measured in the four-momentum transfer squared range 0.23≤−t≤0.67 GeV2. This is the only measurement of the proton-proton elastic cross section in this t range for collision energies above the Intersecting Storage Rings (ISR) and below the Large Hadron Collider (LHC) colliders. We find that a constant slope B does not fit the data in the aforementioned t range, and we obtain a much better fit using a second-order polynomial for B(t). This is the first measurement below the LHC energies for which the non-constant behavior B(t) is observed. The t dependence of B is also determined using six subintervals of t in the STAR measured t range, and is in good agreement with the phenomenological models. The measured elastic differential cross section dσ/dt agrees well with the results obtained at s=540 GeV for proton–antiproton collisions by the UA4 experiment. We also determine that the integrated elastic cross section within the STAR t-range is σelfid=462.1±0.9(stat.)±1.1(syst.)±11.6(scale) μb. © 2024
Keywords: B-slope; Diffraction; Elastic scattering; Proton–proton collisions; dept.phy; peer-reviewed

Measurement of flow coefficients in high-multiplicity 𝑝+Au, 𝑑+Au, and 3 He +Au collisions at √𝑠𝑁⁢𝑁=200 GeV - STAR Collaboration (Physical Review C, 2024)
Flow coefficients (𝑣2 and 𝑣3) are measured in high-multiplicity 𝑝+Au, 𝑑+Au, and 3He+Au collisions at a center-of-mass energy of √𝑠𝑁⁢𝑁=200 GeV using the STAR detector. The measurements utilize two-particle correlations with a pseudorapidity requirement of |𝜂|< 0.9 and a pair gap of |Δ⁢𝜂|>1.0. The primary focus is on analysis methods, particularly the subtraction of nonflow contributions. Four established nonflow subtraction methods are applied to determine 𝑣𝑛, validated using the HIJING event generator. 𝑣𝑛 values are compared across the three collision systems at similar multiplicities; this comparison cancels the final-state effects and isolates the impact of initial geometry. While 𝑣2 values show differences among these collision systems, 𝑣3 values are largely similar, consistent with expectations of subnucleon fluctuations in the initial geometry. The ordering of 𝑣𝑛 differs quantitatively from previous measurements using two-particle correlations with a larger rapidity gap, which, according to model calculations, can be partially attributed to the effects of longitudinal flow decorrelations. The prospects for future measurements to improve our understanding of flow decorrelation and subnucleonic fluctuations are also discussed.
Keywords: dept.phy; peer-reviewed

Production of protons and light nuclei in Au +Au collisions at √𝑠𝑁⁢𝑁=3 GeV with the STAR detector - STAR Collaboration (Physical Review C, 2024)
We report the systematic measurement of protons and light nuclei production in Au +Au collisions at √𝑠𝑁⁢𝑁=3GeV by the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The transverse momentum (𝑝𝑇) spectra of protons (𝑝), deuterons (𝑑), tritons (𝑡), 3He, and 4He have been measured from midrapidity to target rapidity for different collision centralities. We present the rapidity and centrality dependence of particle yields (𝑑⁢𝑁/𝑑⁢𝑦), average transverse momentum (⟨𝑝𝑇⟩), yield ratios (𝑑/𝑝, 𝑡/𝑝,3He/𝑝, 4He/𝑝), as well as the coalescence parameters (𝐵2, 𝐵3). The 4⁢𝜋 yields for various particles are determined by utilizing the measured rapidity distributions, 𝑑⁢𝑁/𝑑⁢𝑦. Furthermore, we present the energy, centrality, and rapidity dependence of the compound yield ratios (𝑁𝑝×𝑁𝑡/𝑁2𝑑) and compare them with various model calculations. The physics implications of these results on the production mechanism of light nuclei and the QCD phase structure are discussed.
Keywords: dept.phy; peer-reviewed

Investigation of experimental observables in search of the chiral magnetic effect in heavy-ion collisions in the STAR experiment - Choudhury, S.; Dong, X.; Drachenberg, J. L.; Dunlop, J. C.; Esumi, ShinIchi; Feng, Yicheng; Finch, E.; Hu, Yu; Jia, Jiangyong; Lauret, Jerome; Li, Wei; Liao, Jinfeng; et al. (Chinese Physics C, 2022)
The chiral magnetic effect (CME) is a novel transport phenomenon, arising from the interplay between quantum anomalies and strong magnetic fields in chiral systems. In high-energy nuclear collisions, the CME may survive the expansion of the quark-gluon plasma fireball and be detected in experiments. Over the past two decades, experimental searches for the CME have attracted extensive interest at the Relativistic Heavy Ion Collider (RHIC) and the Large Hadron Collider (LHC). The main goal of this study is to investigate three pertinent experimental approaches: the correlator, the R correlator, and the signed balance functions. We exploit simple Monte Carlo simulations and a realistic event generator (EBE-AVFD) to verify the equivalence of the core components among these methods and to ascertain their sensitivities to the CME signal and the background contributions for the isobar collisions at the RHIC. © 2022 Chinese Physical Society and the Institute of High Energy Physics of the Chinese Academy of Sciences and the Institute of Modern Physics of the Chinese Academy of Sciences and IOP Publishing Ltd.
11 citations (Crossref) [2023-10-31] https://iopscience.iop.org/article/10.1088/1674-1137/ac2a1f ; http://hepnp.ihep.ac.cn/article/id/55afc331-6758-45b3-97ce-444828b72c70 ; http://cpc.ihep.ac.cn/article/doi/10.1088/1674-1137/ac2a1f ; http://csnsdoc.ihep.ac.cn/article/doi/10.1088/1674-1137/ac2a1f ; https://inspirehep.net/literature/1863127
Keywords: dept.phy; peer-reviewed

ϒ production in U + U collisions at sNN =193 GeV measured with the STAR experiment ϒ PRODUCTION in U + U COLLISIONS at ⋯ L. ADAMCZYK et al. - Adamczyk, Leszek; Adkins, J. K.; Agakishiev, G.; Aggarwal, M. M.; Ahammed, Zubayer; Alekseev, I. G.; Anderson, Derek; Aoyama, Ryo; Aparin, A.; Arkhipkin, D.; Aschenauer, E. C.; Ashraf, Muhammad Usman; et al. (Physical Review C, 2016)
18 citations (Crossref) [2023-10-31] Citation Key Alias: pop00056 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed